PERBEDAAN KUANTITAS DAN KUALITAS SPERMA ANTARA AYAM KETAWA DAN AYAM PELUNG PADA PENAMPUNGAN SPERMA PAGI DAN SORE HARI - , THEODORA WIDI P. R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to compare the quantity and quality fresh sperm in the morning collection and afternoon collection of Ketawa chicken and Pelung chicken. Used six chickens aged Â± 24 weeks consisting of 3 Ketawa chickens and 3 Pelung chickens. Collection of sperm for each chicken was done 10 times with a frequency of 2 times a week, using the massage method. Macroscopic examination of sperm include volume, color and odor, consistency and pH, whereas microscopic examination include motility, viability, abnormality, and the concentration of spermatozoa. Data were analyzed using analysis of variance using a completely randomized design with a types x time of sperm collection factorial pattern. The results showed no difference in odor, color, consistency on both types of cock and sperm at different the morning collection and the afternoon collection. Types of chickens were Ketawa chicken and Pelung chicken had significant effect (Pâ¤0,05) with volume at 0,172Â±0,107 ml, had 7,500Â±0,853 and 6,960Â±0,929 pH and consentration in 1,858Â±1,658.109/ml and 2,803Â±1,517.109/ml. Types of chicken and time of sperm collection had significant (P<0.05) with motility of spermatozoa in 78,833Â±15,574% and 62Â±25,834%. Time of collection had significant effect to viability of spermatozoa in 58,957Â±13,489% and 48,059Â±7,722%. In the volume, pH, sperm viability and concentration there were no interaction between type of chicken and time of collection, but it had in sperm of motility. From these results it could be concluded that the Pelung chicken had quantity and quality of sperm were better than Ketawa chicken , while for the quantity and quality of the sperm with afternoon collecting better than the morning, there were no interaction between types of chicken and time of sperm collection. (Keywords: Differentiation, Quantity, Quality, Sperm, Ketawa chicken, Pelung chicken, Collection time)